Petroleum transportation and production oil spill and pollution control - Sittig, Marshall 1919- (Noyes Data Corp., 1978)
Review of U.S. patents, government reports, and technical journal literature dealing with the control of pollution from the production, transportation, and storage of petroleum products.
Keywords: Umwelt; Oil spills; Petroleum industry and trade -- Environmental aspects -- United States; Petroleum -- Transportation -- Environmental aspects; USA